The New Encyclopedia of Southern Culture : Volume 6: Ethnicity - Ray, R. Celeste (Book collections on Project MUSE., 2007)
Moving beyond racial designations of ""black, "" ""white, "" and ""Indian, "" this volume of The New Encyclopedia of Southern Culture complicates and enriches our understanding of ""southernness"" by demonstrating the extent to which it exists as a fabric of many cultures. This exploration of southern ethnicities examines the ways people ""perform"" their cultural identities through, among other things, dress, dance, and family tradition. Contributors identify 88 major ethnic groups that have lived in the South from the Mississippian Period (1000-1600 C.E.) to the present